The demographics of galactic bulges in the SDSS database - Kim, Keunho; Oh, Sree; Jeong, Hyunjin; Aragón-Salamanca, Alfonso; Smith, Rory; Yi, Sukyoung K. (American Astronomical Society, 2016)
We present a new database of our two-dimensional bulge–disk decompositions for 14,233 galaxies drawn from Sloan Digital Sky Survey DR12 in order to examine the properties of bulges residing in the local universe (0.005 < z < 0.05). We performed decompositions in the g and r bands by utilizing the galfit software. The bulge colors and bulge-to-total ratios are found to be sensitive to the details in the decomposition technique, and hence we hereby provide full details of our method. The g − r colors of bulges derived are almost constantly red regardless of bulge size, except for the bulges in the low bulge-to-total ratio galaxies (B/T r lesssim 0.3). Bulges exhibit similar scaling relations to those followed by elliptical galaxies, but the bulges in galaxies with lower bulge-to-total ratios clearly show a gradually larger departure in slope from the elliptical galaxy sequence. The scatters around the scaling relations are also larger for the bulges in galaxies with lower bulge-to-total ratios. Both the departure in slopes and larger scatters likely originate from the presence of young stars. The bulges in galaxies with low bulge-to-total ratios show signs of a frosting of young stars so substantial that their luminosity-weighted Balmer-line ages are as small as 1 Gyr in some cases. While bulges seem largely similar in optical properties to elliptical galaxies, they do show clear and systematic departures as a function of bulge-to-total ratio. The stellar properties and perhaps associated formation processes of bulges seem much more diverse than those of elliptical galaxies.